The Reductive Amination of Aldehydes and Ketones and the Hydrogenation of Nitriles: Mechanistic Aspects and Selectivity Control - Gomez, Silvia; Peters, Joop A.; Maschmeyer, Thomas (Advanced synthesis & catalysis, 2002)
This review deals with two of the most commonly used methods for the preparation of amines: the reductive amination of aldehydes and ketones and the hydrogenation of nitriles. There is a great similarity between these two methods, since both have the imine as intermediate. However, due to the high reactivity of this intermediate, primary, secondary and/or tertiary amines are obtained (often simultaneously). The relation of the selectivity to different substrate structures and reaction conditions is briefly summarised, the main focus being on the catalyst as it is the most significant factor that governs the selectivity. Different mechanisms are discussed with the view to correlate the structure of the catalyst and, more particularly, the nature of the metal and the support with selectivity. The crucial point is the presumed location of the condensation and hydrogenation steps.